Infective Organism and Antibiotic Sensitivity Analyzed in Chronic Suppurative Otitis Media Patients in Mirpur, AJK (Medical Forum Monthly, 2024)
Objective: To analyze the bacteriological isolates and antibiotics sensitivity for each bacteria causing ear infection resulting in CSOM.A main objective of the study is to avoid excess and incorrect prescription of antibiotics resulting in antibiotic resistance in study area.Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Divisional Headquarter Teaching Hospital Mirpur AJK from April 2012 to December 2014.Materials and Methods: Seventy patients of Chronic Suppurative Otitis Media were evaluated on the basis of bacteriological investigation, culture and sensitivity along with Patient`s parameters like age, clinical features (ear discharge and pain) were documented in the outpatient department of ENT. Informed consent was taken from all the patients. Sample was taken via sterile swabs which were obtained from discharging ear/ears and cultured both aerobically and anaerobically. Sensitivity pattern of causative organism was established according to standard protocols. The antibiotic sensitivity of the confirmed organisms was performed by disk diffusion method (Baurer et al., 1966; Ahmed et al., 2008).Results: Data analysis of CSOM cases during the current study revealed that major CSOM prevalence 70% was in age <30 years and Staphylococcus aureus (67%) was the dominant agent caused CSOM in the study area, followed by the Pseudomonas aeruginosa (17%). Satph. aureus which accounted 57% of chronic otitis media in the study area found 100 sensitive for Ciprofloxacin, Moxifloxacin, Cefixime and Sulzone. While Doxicycline, Rocephin are more than 90% sensitive and Sparfloxacin, Gentamicin, >80% sensitive and Meropenum, Clarithomycin, Cephradine found >70% sensitive for Staph. aureus.Conclusion: Study mainly focused on major causative agents and mean prevalence age for CSOM so that prompt treatment and prevention strategy could be developed in the study area to prevent complications with CSOM.